Optimasi Produksi dan Purifikasi Hidrogen melalui Reformasi Uap Metana pada Reaktor Mikrokanal Menggunakan Simulasi DWSIM dan AspenPlus - Christyanto, Dannar; Sudarmanta, Bambang (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Hydrogen is one of the clean energy vectors with great potential to support the transition toward a sustainable energy system. However, hydrogen production is still predominantly based on fossil-fuel processes, particularly Steam Methane Reforming (SMR), which is endothermic in nature and requires optimal process control to achieve high efficiency and purity. This study aims to optimize the hydrogen production and purification process through steam methane reforming in a microchannel reactor using a simulation-based approach. Microchannel reactors are selected due to their high surface-to-volume ratio, which enhances heat and mass transfer as well as reaction temperature stability. Process simulations were conducted using DWSIM software with the Peng–Robinson thermodynamic model to analyze the effects of operating parameter variations, including reformer temperature, operating pressure, and steam-to-methane ratio, on methane conversion and hydrogen mole fraction. The simulation results indicate that increasing the reformer temperature significantly enhances hydrogen production, reaching optimal conditions in the range of 900–950 °C, where the system approaches thermodynamic equilibrium. The integration of Water Gas Shift and Pressure Swing Adsorption (PSA) units within the simulated system is shown to improve hydrogen purity to above 98%. This study demonstrates that a simulation-based microchannel reactor approach is effective in determining optimal operating conditions and has strong potential to serve as a foundation for the development of efficient, sustainable, small-scale, and modular hydrogen production systems.